2022
DOI: 10.1039/d2ra04318a
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma driven self-assembly in serum proteins: insights into the protein aggregation to biomaterials

Abstract: Self-assembly of proteins after CAP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It is reported that an electron-rich environment is associated with a decrease in tryptophan fluorescence. [35,60] As a result of the interaction between the fibrinogen and very electronrich CAP with varying feed gases Oxygen, Argon, and Helium, the CAP treatment has caused quenching. [60] The quenching is of the following order Oxygen> Helium> Argon.…”
Section: Fluorescence Studies Of Fibrinogen After Cap Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that an electron-rich environment is associated with a decrease in tryptophan fluorescence. [35,60] As a result of the interaction between the fibrinogen and very electronrich CAP with varying feed gases Oxygen, Argon, and Helium, the CAP treatment has caused quenching. [60] The quenching is of the following order Oxygen> Helium> Argon.…”
Section: Fluorescence Studies Of Fibrinogen After Cap Treatmentmentioning
confidence: 99%
“…[27,28] Several studies have already shown a beneficial effect of CAP on blood coagulation and wound healing. [29][30][31][32][33][34] Investigation of CAP-protein interaction has also been carried out for different protein molecules like myoglobin, lysozyme, and serum albumin, [35][36][37] due to their imperative role in the wound healing process. Studies also suggest that CAP plays a crucial role in changing the structural properties of different protein molecules leading to aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] CAPP generates controllable amounts of ROS and RNS that are transported to react with biological targets including cells and tissues for cancer treatment, 22 sterilization of wound tissue, 23,24 corneal infections treatment, 25 instantaneous blood coagulation, 26 leishmaniosis, 27 treatment of dental diseases 28 and protein modications. 29,30 Other application areas CAPPs include material etching, 31 depositions, 32 surface modication, 33 degradation of pollutants, 34,35 decontamination of microorganisms in water, 36,37 synthesis of nanomaterials, 38,39 etc., however, its usability in the formation of new materials in aqueous systems still needs more exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Upon plasma exposure, TA react with OH − and creates uorescent hydroxy terephthalic acid (HTA), and the excitation/emission maxima for the formation of HTA are 312/ 423 nm. 21,30 The H 2 O 2 concentration was measured using red uorescence uorometric hydrogen peroxide assay kit by Sigma-Aldrich. NO, NO 2 − and NO The plasma treatment led to the oxidation of electron-rich groups in amino acids by various active species.…”
mentioning
confidence: 99%
See 1 more Smart Citation